Scandal and silence media responses to presidential misconduct - Entman, Robert M. (Cambridge, UK Polity Press, 2012)
The author argues that "media neglect most corruption, providing too little, not too much scandal coverage; scandals arise from rational, controlled processes, not emotional frenzies -- and when scandals happen, it's not the media but government and political parties that drive the process and any excesses that might occur; significant scandals are difficult for news organizations to initiate and harder for them to maintain and bring to appropriate closure; for these reasons cover-ups and lying often work, and truth remains essentially unrecorded, unremembered."--Back cover
High crimes or misdemeanors? -- Analyzing media and presidential scandal -- Private lives in the public sphere : what do journalists know, and when do they tell it? -- Secret sins of 2008 : the McCain, Edwards and Clinton families' values -- Dodging scandals--and the draft -- Rathergate : from a scandal of politics to a scandal of journalism -- Harkening to other matters : what news looks like when a scandal is silenced -- Silenced scandals of grave misconduct -- Recalibrating scandal and silence.
Includes bibliographical references (pages [234]-255) and index.
Keywords: Scandals in mass media; Mass media -- Political aspects; Scandals -- Press coverage -- United States; Presidents -- Press coverage -- United States; Presidents -- Corrupt practices -- United States -- History; Presidents -- Sexual behavior -- United States -- History; Scandals -- United States